Antioxidant Enzymes and Heat-Shock Protein Genes of Green Peach Aphid (Myzus persicae) Under Short-Time Heat Stress - Khurshid, Aroosa; Inayat, Rehan; Tamkeen, Ansa; Ul Haq, Inzamam; Li, Chunchun; Boamah, Solomon; Zhou, Jing-Jiang; Liu, Changzhong (Frontiers in Physiology, 2021)
The management of insect pests under fluctuating temperature has become an interest area of study, due to their ability to stimulate defense mechanisms against heat stress. Therefore, understanding insect’s physiological and molecular response to heat stress is paramount for pest management. Aphids are ectodermic organisms capable of surviving in different climatic conditions. This study aimed to determine the effects of short-time heat stress on green peach aphid Myzus persicae under controlled conditions. In this study short-time, heat stress treatments at different temperatures 27, 30, 33, and 36 °C with an exposure time of 1, 3, 6, and 10 h on the activities of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT), peroxidases (POD) and oxidants such as malondialdehyde (MDA), and hydrogen peroxide (H2O2) were determined. The results showed that the short-time heat stresses significantly increased the MDA content of M. persicae by 71%, 78%, 81%, and 86% at 36 oC for the exposure times of 1, 3, 6 and 10 h, respectively, compared to control. The content of H2O2 increased by 75%, 80%, 85% and 88% at 36 °C for the exposure time of 1, 3, 6, and 10 h respectively compared to control. The SOD, POD and CAT activity increased by 61%, 76%, 77% for 1 h; 72%, 83%, 84% for 3 h, 80%, 85%, 86% for 6 h and 87%, 87.6%, 88% for 10 h at 36 °C respectively compared to control. Again, under short time heat stress the transcription levels of Hsp22, Hsp23, Hsp27, SOD, POD and CAT genes were upregulated compared to control. Our results suggest that M. persicae increased the enzymatic antioxidants activity and heat-shock genes expression as one of the defensive mechanisms in response to heat stresses.